Factors contributing to productivity in the South African electronic manufacturing industry - Ramhari, Vinay (My University, 2018)
Electronic manufacturing services companies play an important role in the SouthAfrican economy and society. They contribute to the growth of the country andprovides sustainable jobs to the community.The purpose of this reseach was to identify the perceived factors that contributed toproductivity, either negative or positive, within the electronic manufacturing industry inSouth Africa. By identifying these factors and making it known, leaders in the industrycan make use of the information to improve their levels of productivity within theirorganisations.A quantitative approach was taken in this research and data was gathered through aLikert scale survey on the electronic manufacturing services industry within SouthAfrica. From the literature review, 12 broad variables were identified as contributingfactors to productivity. The research concluded that six of the 12 variables contributedto productivity negatively. These six variables were grouped broadly into three factorcategories, namely Skills, Process and Preventative measures.The outcome of this study highlights the main contributors to poor productivity and theindustry will now be aware of these factors. This gives management within this sectorthe opportunity to focus on these factors to improve the levels of productivity withintheir organisations.
MBA
Keywords: Electronic data interchange. Organizational change.